2011
DOI: 10.1017/s0272263110000549
|View full text |Cite
|
Sign up to set email alerts
|

Across Languages, Space, and Time

Abstract: This review examines whether similarity between the first language (L1) and second language (L2) influences the (morpho)syntactic processing of the L2, using both neural location and temporal processing information. Results from functional magnetic resonance imaging (fMRI) and event-related potential (ERP) studies show that nonnative speakers can exhibit nativelike online L2 (morpho)syntactic processing behavior and neural patterns. These findings are contrary to predictions of the shallow structure hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 70 publications
(197 reference statements)
7
17
0
Order By: Relevance
“…Although there were no differences in the learner groups behaviourally (offline), the differences in the ERP effects (online) indicated that L2 learners whose L1 has a similar word order seem to use similar neurological substrates as native speakers to process the L2. Importantly, these findings extend the results from other ERP studies exploring effects of the L1 on L2 processing of morphosyntax (Dowens et al, 2011;Dowens et al, 2010;Sabourin & Stowe, 2008) to syntactic structures showing that similarities in the L1 and L2 are more likely to yield similar ERP responses than structures that are not (for overviews see Caffarra, Molinaro, Davidson & Carreiras, 2015;Morgan-Short, 2014;Tolentino & Tokowicz, 2011;van Hell & Tokowicz, 2010). The findings therefore also suggest that the developmental trajectory of online word order processing in a second language may depend on whether the first and second language show similarities (more L1-L2 similarities should lead to faster nativelike processing), even if the development of offline comprehension shows no such influence.…”
Section: Discussionsupporting
confidence: 82%
“…Although there were no differences in the learner groups behaviourally (offline), the differences in the ERP effects (online) indicated that L2 learners whose L1 has a similar word order seem to use similar neurological substrates as native speakers to process the L2. Importantly, these findings extend the results from other ERP studies exploring effects of the L1 on L2 processing of morphosyntax (Dowens et al, 2011;Dowens et al, 2010;Sabourin & Stowe, 2008) to syntactic structures showing that similarities in the L1 and L2 are more likely to yield similar ERP responses than structures that are not (for overviews see Caffarra, Molinaro, Davidson & Carreiras, 2015;Morgan-Short, 2014;Tolentino & Tokowicz, 2011;van Hell & Tokowicz, 2010). The findings therefore also suggest that the developmental trajectory of online word order processing in a second language may depend on whether the first and second language show similarities (more L1-L2 similarities should lead to faster nativelike processing), even if the development of offline comprehension shows no such influence.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are broadly compatible with existing evidence about L1 effects during L2 processing (e.g. Sanoudaki & Thierry, 2014;Tolentino & Tokowicz, 2011). However, further research is required to examine whether a) this coactivation is unique to mixed language tests (our CMTs and SPR both included an L1 context and L2 stimulus) and b) current findings would hold for tests only presented in the L2.…”
Section: Observation Of Online Effectssupporting
confidence: 90%
“…There is also growing evidence of L1 coactivation/influence during online L2 sentence processing (e.g. Tolentino & Tokowicz, 2011). Tokowicz and WarrenÕs (2010) self-paced reading study with beginner learners reported slower reading times at morphosyntactic violations for L2 Spanish features that were cross-linguistically similar (verb aspect licensing), but not for those that were entirely unique to the L2 (determinerÐnoun gender agreement).…”
Section: Accepted For Publication Studies In Second Language Acquisimentioning
confidence: 99%
See 1 more Smart Citation
“…Prior neuroimaging studies indicate that RLD certainly has some consequences for bilinguals, especially with regards to how each language is neurally represented and processed vis-a-vis the other. Linguistic features specific to one language can require additional or specialized neural resources (such as processing tonal vs. non-tonal phonemes), which can give rise to functionally different neural processing profiles for each language in the bilingual brain (e.g., Bick et al, 2011;Mei et al, 2015;Perfetti et al, 2007;Green et al, 2007;Tolentino & Tokowicz, 2011). However, despite language combinations/RLD being an obvious point of variation among bilinguals and a distinguishing dimension of the bilingual experience, its possible contribution to the bilingual experience has not received a lot of attention (Bialystok, 2017).…”
Section: Language Distance Does Matter For Bilingual Neurobiology Andmentioning
confidence: 99%